Czy robot może stać się człowiekiem poprzez język? Analiza funkcji językowych pewnego bota - Fainstein, Jolanta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article analyzes the statements of the main character of the series "Better than we" from the point of view of selected linguistic functions (informative, phatic, appellative, emotive, poetic and social) in order to check whether they can be a sign of humanity, or whether they can be its linguistic measure. The analysis of the main character`s dialogues from the point of view of linguistic functions shows that as the plot of the series becomes denser, during which Arisa becomes a part of the community, apart from the linguistic functions typical of ordinary bots, the functions focused on emotions come to the fore and significantly dominate in subsequent dialogues with the participation of the heroine.
Keywords: funkcje językowe; emocje; uczucia; komunikacja; społeczność; linguistic functions; emotions; feelings; communication; community